The aged in three western societies - Friis, Henning (Statistical and Social Inquiry Society of Ireland, 1966)
'A comparative social survey on living conditions and behaviour of the aged in Denmark, Great Britain and U.S.A.'- subtitle. Through the last fifteen years important new territory has been conquered in social gerontology in most of the countries of the Western world. Social gerontology is, however, still at an early stage of development. Most countries lack basic facts on many aspects of the life of elderly people, and theoretical generalizations regarding the social factors in the aging process are only beginning to be established. The result is that a number of untested stereotypes and myths have grown up round the elderly in Western countries.
Read before the Society, 12th January 1966.
Keywords: Social gerontology; Economics of the elderly; Retirement; Pensions; 314.15